Descripción del pichón de Xenopsaris albinucha - Di Giacomo, Alejandro G. (2000)
We report the first record on the nesting of the White-naped Xenopsaris (Xenopsaris albinucha) for Buenos Aires Province. The nestling are described and commented. The mouth color is pink, a rare characteristic in the suboscines.